Kick Andy sebagai Media Inspiratif dalam Menanamkan Nilai-Nilai Pancasila pada Generasi Muda Indonesia - Bakara, Gressi Naftali; Wibowo, Rizky Aji; Hanif, Utsman; Martani, Salama Arzu; Sianipar, Jessy Novelia; Sabrina, Ananda Paula; Nurvika, Febrianti; Adhipramana, Muhammad Hafizh; Rainchany, Kaisya; Siahaan, Nathania Christabel (Oratio Directa (Prodi Ilmu Komunikasi), 2025)
Kick Andy is widely recognized as a television program that presents real-life inspirational stories from various segments of Indonesian society. Amidst the dominance of sensational entertainment media, Kick Andy offers content that promotes moral values and motivation. This study aims to analyze how Kick Andy serves as an unlimited source of inspiration for Indonesian youth in shaping character, encouraging creativity, and fostering social awareness. The research uses a qualitative approach with a descriptive method. Data were obtained from documentation of selected Kick Andy episodes, content observation, and relevant literature. Data collection techniques included content analysis and documentation. The findings indicate that through touching narratives, exemplary figures, and a humanistic approach, Kick Andy has a positive influence on character development and inspiring change among young people. The program proves to be an alternative form of media that not only entertains but also educates and inspires.Keywords: Kick Andy, youth, inspiration, positive media, character building